2014
DOI: 10.1155/2014/547974
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Urban Heat Island Effect in Megacity Tehran

Abstract: Cities demonstrate higher nocturnal temperatures than surrounding rural areas, which is called “urban heat island” (UHI) effect. Climate change projections also indicate increase in the frequency and intensity of heat waves, which will intensify the UHI effect. As megacity Tehran is affected by severe heatwaves in summer, this study investigates its UHI characteristics and suggests some feasible mitigation strategies in order to reduce the air temperature and save energy. Temperature monitoring in Tehran shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 36 publications
(34 reference statements)
1
46
0
4
Order By: Relevance
“…These results go with other recently published study, which suggests that the combination of vegetation and green roofs can reduce the temperature from around 295K to 294.20K [51]. Additionally, M. Burse and J. Carol found that combining green-roofs with street-level vegetation can reduce the air temperature uniform ally with a maximum of 2.4K.…”
Section: E Green-roof Casesupporting
confidence: 91%
See 1 more Smart Citation
“…These results go with other recently published study, which suggests that the combination of vegetation and green roofs can reduce the temperature from around 295K to 294.20K [51]. Additionally, M. Burse and J. Carol found that combining green-roofs with street-level vegetation can reduce the air temperature uniform ally with a maximum of 2.4K.…”
Section: E Green-roof Casesupporting
confidence: 91%
“…Several studies show that the maximum temperature difference between the inside and outside of the small green area can be 3K [51]. Accordingly, we have compared the temperature and the relative humidity of the measuring site between the two measuring points in the site to estimate green-vegetation cover impact on the temperature reduction.…”
Section: B Measurements Resultsmentioning
confidence: 99%
“…In recent decades, Tehran has been experiencing environmental problems, such as UHI [31][32][33] and urban air pollution (UAP) [34,35] that has impacted the health and even endangered the lives of local residents. UHI and UAP have a common source and interact with each other [4,8].…”
mentioning
confidence: 99%
“…This megacity has a large, densely populated area of 750 km 2 (Sodoudi et al 2014). It is located in valleys and is surrounded to the north, northwest, east and southeast by mountains with heights between 1000 and 3800 m (Madanipour 2006).…”
Section: Case Studymentioning
confidence: 99%